Numerical conformal mapping onto the exterior unit disk with a straight slit and logarithmic spiral slits - Murid A.H.M.; Yunus A.A.M.; Nasser M.M.S. (Institute of Physics Publishing, 2024)
This paper presents a fast boundary integral equation method for numerical conformal mapping of unbounded multiply connected regions onto a disk with an infinite straight slit and finite logarithmic spiral slits. Some numerical examples are given to show the effectiveness of the proposed method.